Cataract surgery and subtype in a defined, older population: the SEECAT Project. Issue 12 (17th November 2004) - Lewis, A; Congdon, N; Munoz, B; Bowie, H; Lai, H; Chen, P; West, S K
Abstract : Aim: To describe the distribution of cataract subtypes present before surgery among a defined population of older, bilaterally pseudophakic individuals. Methods: This was a cohort study of bilaterally pseudophakic individuals participating in the Salisbury Eye Evaluation (SEE), and their locally resident siblings. Subjects underwent slit lamp and retroillumination photography and grading using the Wilmer Cataract Grading System. For all individuals determined to be bilaterally pseudophakic, an attempt was made to determine for each eye the type(s) of cataract present before surgery, based on previous SEE photographs (for SEE participants) and/or medical records obtained from the operating ophthalmologist (for both SEE participants and their siblings). Results: The mean age of 223 participants providing data in this study was 78.7 (SD 5.2) years, 19.3% of subjects were black and 60.1% female. The most common surgically removed cataract subtype in this population was pure nuclear (43.5%), followed by nuclear combined with posterior subcapsular cataract (PSC) (20.6%), and nuclear combined with cortical (13.9%); less common types were pure cortical (4.9%), pure PSC (4.5%), and PSC combined with cortical (2.7%). Factors such as sex and source of lens data (study photograph versus clinical record) did not significantly affect the distribution of lens opacity types, while PSC was significantly (p = 0.01) more common among younger people and nuclear cataract was significantly (p = 0.001) more common among white compared to black people. Conclusion: Epidemiological studies have suggested that the different subtypes of cataract are associated with different risk factors. As studies begin to identify new prevention strategies for cataract, it would appear likely that different strategies will be efficacious against different types of cataract. In this setting, it will be helpful to know which cataract types are most frequently associated with surgery. Among this older, majority white population, nuclear cataract showed a clear predominance among individuals having undergone surgery in both eyes. This may be contrasted with both clinic and population based studies of younger people, which have generally found PSC cataract to predominate.